Kevin P. Spicer and Rebecca Carter-Chand, Eds. Religion, Ethnonationalism, and Antisemitism in the Era of the Two World Wars - Griech-Polelle, Beth (Studies in Christian-Jewish Relations, 2022)
No abstract is available.